CLASSIFICATION OF INNOVATIVE STRATEGIES OF INDUSTRIAL ENTERPRISES - Yuldasheva Nilufar Abduvakhidovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the classification of innovative strategies of industrial enterprises is considered in detail. It is substantiated that there is a need for a systematic study of existing approaches, and comprehensive classification of innovative strategies has been developed. It is argued that the innovation strategy is the basis of the overall strategy and, at the same time, the main condition for the competitive development of the enterprise. The formation of a corporate competitive strategy by using the achievements of innovative management is based on the interaction between the external environment, a functioning system (organization), which strives for stability, and the management system, which ensures the adaptation of the organization to the operating conditions (to the external environment). Large companies that use the system of strategic innovation planning have the opportunity to constantly implement innovative activities according to a certain scheme (or strategy). According to modern international standards, innovations are permanent when they are implemented at least once every 1 to 3 years. In addition, it is common for large companies to use a combination of several strategic lines, which ensures high mobility and innovation efficiency.